Voter polling backroom
A group of women working in a polling station located in a backroom at 780 Irene Street, San Jose. From left to right: Christine "Tiny" Albanese McArthur, Vera Antuzzi Lema, Flora Albanese Talesfore, Tina Massa Kuykendal, Clotilda O'Reilly (foreground, white sweater), (?).